Communication apprehension and academic performance among undergraduates at a Malaysian Public University - Teo, Tammy Ching Sin (Universiti Malaysia Sarawak (UNIMAS), 2015)
This research investigated the relationship between Communication Apprehension (CA) and Academic Performance (AP) among undergraduates. The influence of demographic factors such as gender and ethnicity on the relationship between CA and AP was also investigated. Other factors such as Cognitive Style (CS) and Personality Traits (PT) which may impact on the relationship between CA and AP among undergraduates were also investigated. The research design used in the study was a "Cross-Sectional Survey" with correlational and comparative analyses. The sample in this study consisted of 250 undergraduates who were enrolled in the Bachelor of Science (Cognitive Science) program at the Faculty of Cognitive Sciences and Human Development, University Malaysia Sarawak (UNIMAS). Three instruments were used to collect the data in this research namely Personal Report of Communication Apprehension (PRCA-24), Group Embedded Figures Test (GEFT) and Introversion Scales. Chi-square tests of independence were used to determine the relationship between CA and AP. The findings of this study showed that there was no association between CA level and AP among undergraduates. Besides, the Chi-square tests of independence was also used to determine the relationship between CA and gender, CA and ethnicity, CA and AP based on CS, and lastly, CA and AP based on PT. The study found that there was no association between CA level and gender among undergraduates. The results also showed that there was no association between CA level and ethnicity among undergraduates. On the other hand, the results showed that there was an association between CA and AP for field-mixed undergraduates. Lastly, these results showed that there was no association between CA and AP based on PT. The findings of these results will provide useful insight to assist educators of learning institutions in helping learners overcome the issue ofCA as it might affect the learners' learning process and career development